Effect of High‐Calcium Diet on Coronary Artery Disease in Ossabaw Miniature Swine With Metabolic Syndrome. Issue 8 (13th August 2015) - Phillips‐Eakley, Alyssa K.; McKenney‐Drake, Mikaela L.; Bahls, Martin; Newcomer, Sean C.; Radcliffe, John S.; Wastney, Meryl E.; Van Alstine, William G.; Jackson, George; Alloosh, Mouhamad; Martin, Berdine R.; Sturek, Michael; Weaver, Connie M.
Abstract : Background: Calcium is a shortfall essential nutrient that has been a mainstay of osteoporosis management. Recent and limited findings have prompted concern about the contribution of calcium supplementation to cardiovascular risk. A proposed mechanism is through the acceleration of coronary artery calcification. Determining causality between calcium intake and coronary artery calcification has been hindered by a lack of sensitive methodology to monitor early vascular calcium accumulation. The primary study aim was to assess the impact of high calcium intake on coronary artery calcification using innovative calcium tracer kinetic modeling in Ossabaw swine with diet‐induced metabolic syndrome. Secondary end points (in vitro wire myography, histopathology, intravascular ultrasound) assessed coronary disease. Methods and Results: Pigs (n=24; aged ≈15 months) were fed an atherogenic diet with adequate calcium (0.33% by weight) or high calcium (1.90% from calcium carbonate or dairy) for 6 months. Following 5 months of feeding, all pigs were dosed intravenously with 41 Ca, a rare isotope that can be measured in serum and tissues at a sensitivity of 10 −18 mol/L by accelerator mass spectrometry. Kinetic modeling evaluated early coronary artery calcification using 41 Ca values measured in serial blood samples (collected over 27 days) and coronary artery samples obtained at sacrifice. Serum disappearance of 41 Ca and total coronary artery 41 Ca accumulation did not differ among groups. Secondary end points demonstrated no treatment differences in coronary artery disease or function. Conclusion: There was no detectable effect of high calcium diets (from dairy or calcium carbonate) on coronary artery calcium deposition in metabolic syndrome swine.